The Potential of Stability of Domestic Social Political Stability in the Industrial Relations Court (Taken From the Case of Unilateral Wage Increase Dispute & Violation of the Employment Agreement) - Harrys Pratama Teguh; Ru’fah Abdullah (LEGAL BRIEF, 2022)
Creating a harmony in life is the main goal of all human beings to be achieved, but it is very difficult to be fulfilled and felt by the whole community both before and after the implementation Undang Undang Nomor 11 Tahun 2020 About Cipta Kerja which was marked by the spread of the outbreak in 2019 Novel Coronavirus known as Covid 19. Seen in the political arena, if the government is unable to control the curve of increasing positive cases of Covid-19, then public anxiety about the threat of Covid-19 will still be high which will trigger the overall productivity of the community to decrease and unemployment to increase, so that people's incomes are aggregated. will decrease and poverty will certainly increase accompanied by a political crisis so that national political stability will be increasingly problematic.Based on the research background above, the identification in this study is as follows: 1). What are the Factors Affecting the Shaking of Socio-Political Stability Associated with a Unilateral Wage Increase by an Employer or an Entrepreneur? 2). What are the next steps in responding to the Shaking of Domestic Socio-Political Stability following the issuance of Law Number 11 of 2020 about Cipta Kerja In the era of President Joko Widodo ? In accordance with the background and identification of the problem, the objectives of this study are: 1). To find and analyze the factors that influence the shaking of socio-political stability associated with unilateral termination of employment by an employer or an entrepreneur. 2) To find and analyze future steps in responding to the Shaking of Domestic Socio-Political Stability over the enactment of Law Number 11 of 2020 about Cipta Kerja In the era of President Joko Widodo. This research is a doctrinal legal research, the doctrinal law research in question is research that places the law in a construction of a norm system in accordance with legal norms that apply to positive legal provisions, namely the Ius Constitutum principle by using a normative juridical approach, namely inventorying, reviewing and analyzing and understanding the law as a set of rules or positive norms in the legal system that regulates human life which is colored by various symptoms and facts contained in social life in depth. Based on the results of the study in accordance with the identification of the problem in the study, it can produce a conclusion that is not far from the identification of the problem, namely as follows: Government Regulations, Company Capability, Position and Responsibilities, Term of Service, and Productivity & Job Appraisal. The next step in responding to the Shaking of Domestic Socio-Political Stability with the issuance of Law Number 11 of 2020 about Cipta Kerja In the era of President Joko Widodo, which until now, there are still many regions that do not have/have a Bipartite Institution in accordance with the regulations Pasal 106 UU Number 13 tahun 2003 about Ketenagakerjaan.